Effect of plant biostimulants on nutritional and chemical profiles of almond and hazelnut - Pascoalino, Liege (2018)
The increasing interest in natural foods with functional effects demands progressively higher production levels. Nonetheless, there is an orientation towards practicing more sustainable agriculture, free from environmentally harmful pesticides and fertilizers. Plant biostimulants, a class of bio-based agriculture products designed to improve crop development, represent a feasible alternative to chemical fertilizers, or, at least, an effective way of reducing the employed quantities. Herein, different types of plant biostimulants compatible with organic farming (Phytoalgae, Foliar B, Amino Acids, Soil B, Fitoalgas Green® and Sprint Plus®) were tested in two of the most important nut products worldwide: almonds and hazelnuts, which were tested for nutritional parameters, fatty acids profiles and tocopherols contents. Overall, the most notorious effects in almond samples were obtained with phytoalgae (seaweed Ascophyllum nodosum extracts), particularly reflected in the upraising around 10% of γ-tocopherol and β-tocopherol contents. Likewise, hazelnuts treated with NPK + phytoalgae were also characterized by an increase of almost 18% in tocopherols levels, while treatment with NPK alone induced 15.1% higher percentage of linoleic acid.